Synthesis and applications of natural fiber‐reinforced epoxy composites: A comprehensive review - Md. Zobair Al Mahmud; S. M. Fazle Rabbi; Md. Didarul Islam; Nayem Hossain (SPE Polymers)
Abstract This review aims to provide a detailed analysis of the synthesis methods, properties, and applications of natural fiber‐reinforced epoxy composites, highlighting their potential as sustainable materials for various industries. The objective of the study is to examine how different natural fibers such as jute, flax, hemp, and sisal impact the mechanical performance of epoxy composites. The synthesis of these composites involves fiber selection, surface treatments, and epoxy matrix formulation, with processing techniques like hand lay‐up, vacuum infusion, and compression molding playing critical roles. Quantitative results show that tensile strengths of these fibers range from 12 MPa (abaca) to 1627 MPa (pineapple), and densities range from 295 kg/m3 (kenaf) to 1560 kg/m3 (pineapple), reflecting their variability and influence on composite performance. The review finds that fiber‐matrix compatibility, fiber orientation, and interfacial adhesion significantly affect the mechanical properties, such as tensile strength and thermal stability. The composites demonstrate potential applications in the automotive, aerospace, and construction industries, where they can be used for interior components, structural elements, and non‐load‐bearing parts. The study concludes that natural fiber‐reinforced epoxy composites offer a promising solution for reducing environmental impact while maintaining material performance in various structural applications. Highlights Epoxy‐reinforced natural fiber composites synthesis and applications. Synthesis involves fiber selection, treatment, and epoxy matrix formulation. Natural fibers like jute, flax, hemp, and sisal used due to their renewable nature and biodegradability. Applications include automotive and furniture industries.